Motivations, barriers, and enablers for demand response programs: A commercial and industrial consumer perspective. (August 2022) - Lashmar, N.; Wade, B.; Molyneaux, L.; Ashworth, P.
Abstract: Increasing variable renewable generation and consumer peak demand has brought about challenges for electricity utilities to balance supply and demand efficiently and economically. Consumer demand response is one solution for providing balancing services, with large industrial businesses providing these services in many electricity markets. However, there are many barriers to commercial and industrial consumers participating in demand response. Reported barriers are presented from utility and market perspectives, with a gap in understanding the barriers for consumers participation. This article presents the results of a literature review and interviews with commercial and industrial consumers participating in demand response, to identify the barriers and motivations for participation, and factors that enable action. This article contributes to the literature on demand response by presenting empirical evidence, which identifies new, and confirms and challenges previously reported motivations and barriers. We confirm financial benefits are the primary motivation with few consumers making the link between their participation in demand response and providing balancing services to prevent blackouts and manage variable renewable generation. With growing investor focus on environmental sustainability we assert there is opportunity to communicate these non-financial benefits providing additional value to existing and potential customers. Finally, we identify businesses are overcoming some barriers using enabling strategies however need further assistance with barriers which prevent participation, including awareness of demand response programs with flexible requirements. Understanding these motivations and barriers, and enabling strategies used to overcome these barriers, will assist market participants to develop interventions and better engage consumers in demand response. Highlights: C&I consumers motivated by financial benefits but many unaware of system and community benefits. Confirmation and challenging of existing barriers and identification of new, such as P&E tolerances. Improving availability of demand response programs with flexible requirements to improve participation.